Pupils’ Attitude to the Subject of Chemistry at Secondary Vocational Schools - Rusek, Martin (Scientia in educatione, 2020)
This paper is a contribution to the process of mapping the education reality at nonchemical vocational schools. The main objective of this article was to investigate nonchemical vocational schools students’ attitudes towards Chemistry like science and like a school subject. Further, the students’ orientation in the content of the subject and their opinion of usefulness of the findings for their life is investigated. Results of the orientation survey are set into present findings about the educational reality at this type of schools. The implications of results are also used as the basis for futher research.